Dendrimers bind antioxidant polyphenols and cisplatin drug. - Amine Abderrezak (Public Library of Science (PLoS), 2012)
Synthetic polymers of a specific shape and size play major role in drug delivery systems. Dendrimers are unique synthetic macromolecules of nanometer dimensions with a highly branched structure and globular shape with potential applications in gene and drug delivery. We examine the interaction of several dendrimers of different compositions mPEG-PAMAM (G3), mPEG-PAMAM (G4) and PAMAM (G4) with hydrophilic and hydrophobic drugs cisplatin, resveratrol, genistein and curcumin at physiological conditions. FTIR and UV-visible spectroscopic methods as well as molecular modeling were used to analyse drug binding mode, the binding constant and the effects of drug complexation on dendrimer stability and conformation. Structural analysis showed that cisplatin binds dendrimers in hydrophilic mode via Pt cation and polymer terminal NH(2) groups, while curcumin, genistein and resveratrol are located mainly in the cavities binding through both hydrophobic and hydrophilic contacts. The overall binding constants of durg-dendrimers are ranging from 10(2) M(-1) to 10(3) M(-1). The affinity of dendrimer binding was PAMAM-G4>mPEG-PAMAM-G4>mPEG-PAMAM-G3, while the order of drug-polymer stability was curcumin>cisplatin>genistein>resveratrol. Molecular modeling showed larger stability for genisten-PAMAM-G4 (ΔG = -4.75 kcal/mol) than curcumin-PAMAM-G4 ((ΔG = -4.53 kcal/mol) and resveratrol-PAMAM-G4 ((ΔG = -4.39 kcal/mol). Dendrimers might act as carriers to transport hydrophobic and hydrophilic drugs.